The Benefit of Attention-to-Memory Depends on the Interplay of Memory Capacity and Memory Load - Lim, Sung-Joo; Wöstmann, Malte; Geweke, Frederik; Obleser, Jonas (Frontiers in Psychology, 2018)
Humans can be cued to attend to an item in memory, which facilitates and enhances the perceptual precision in recalling this item. Here we demonstrate that this facilitating effect of attention-to-memory hinges on the overall degree of memory load. The benefit an individual draws from attention-to-memory depends on her overall working memory performance, measured as sensitivity (d’) in a retroactive cue (retro-cue) pitch discrimination task. While listeners maintained 2, 4, or 6 auditory syllables in memory, we provided valid or neutral retro-cues to direct listeners’ attention to one, to-be-probed syllable in memory. Participants’ overall memory performance (i.e., perceptual sensitivity d’) was relatively unaffected by the presence of valid retro-cues across memory loads. However, a more fine-grained analysis using psychophysical modelling shows that valid retro-cues elicited faster pitch-change judgments and improved perceptual precision. Importantly, as memory load increased, listeners’ overall working memory performance correlated with inter-individual differences in the degree to which precision improved (r = 0.39, p = 0.029): Under high load, individuals with low working memory profited least from attention-to-memory. Our results demonstrate that retrospective attention enhances perceptual precision of attended items in memory but listeners’ optimal use of informative cues depends on their overall memory abilities.